New species and morphological notes on the termitophilous genera Fonsechellus Silvestri and Oecidiophilus Silvestri from Brazil (Staphylinidae, Aleocharinae, Corotocini, Termitoceina) - Zilberman, Bruno (2020)
Fonsechellus Silvestri and Oecidiophilus Silvestri consist of two Neotropical genera of termitophilous rove beetles, which have been poorly characterized due to the scarcity of material for studies. Herein, based on material collected in the seventies and housed in the Museu de Zoologia da Universidade de São Paulo, two new species associated with Atlantitermes guarinim Fontes and Diversitermes sp., are described and illustrated: Fonsechellus heterosetosus sp. nov. and Oecidiophilus cleidecostae sp. nov., respectively. The latter represents the first record of the genus to Brazil. Also, Fonsechellus fragilis and F. fontesi are redescribed, and a key for species identification is provided for the genus. The condition of the membranous wings of Fonsechellus is addressed and discussed, and the definition of both genera is expanded.